2013
DOI: 10.1039/c3dt32865a
|View full text |Cite
|
Sign up to set email alerts
|

X-ray transient absorption structural characterization of the 3MLCT triplet excited state of cis-[Ru(bpy)2(py)2]2+

Abstract: The excited state dynamics and structure of the photochemically active complex cis-[Ru(bpy)2(py)2](2+) have been investigated using optical transient absorption (OTA) and X-ray transient absorption (XTA) spectroscopy, and density functional theory (DFT). Upon light-excitation in aqueous solution cis-[Ru(bpy)2(py)2](2+) undergoes ultrafast dissociation of one pyridine ligand to form cis-[Ru(bpy)2(py)(H2O)](2+). OTA measurements highlighted the presence of two major time components of 1700 ps and 130 ps through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 50 publications
7
53
0
Order By: Relevance
“…In the case of 3 and 7, their X-ray structures were previously solved [17] and the calculated geometries display a good agreement with them, although bond distances and angles are somewhat overestimated by calculations as demonstrated previously for other systems [33].…”
Section: Structural Properties Of Complexes 1-7supporting
confidence: 75%
“…In the case of 3 and 7, their X-ray structures were previously solved [17] and the calculated geometries display a good agreement with them, although bond distances and angles are somewhat overestimated by calculations as demonstrated previously for other systems [33].…”
Section: Structural Properties Of Complexes 1-7supporting
confidence: 75%
“…This technique has previously provided a detailed understanding of the pathways involved in photoactivation of this type of Ru II complex. 21,22 Efficient population of a dissociative triplet metal-centered ( 3 MC) state is key to generating high quantum yields of a penta-coordinate intermediate (PCI) species, which in turn may form the target species: a mono-aqua photoproduct. We showed that photoactivation of cis -[Ru(bpy) 2 (NA) 2 ] 2+ to cis -[Ru(bpy) 2 (NA) (H 2 O)] 2+ (NA = nicotinamide) occurs with a quantum yield ≥0.36, all within a timeframe of ∼400 ps.…”
Section: Resultsmentioning
confidence: 99%
“…We determined the 3 MLCT ES structure of cis-[Ru(bpy) 2 (py) 2 ] 2+ and complemented our previous TR-XSS characterization with a 100 ps resolution TR-EXAFS experiment performed at the 11-ID-D beamline of the APS (see §4d) [283].…”
Section: Discussionmentioning
confidence: 99%